Why has there been a fall in child labor and an increase in school attendance in Mexico? - Valero Gil, Jorge Noel; Valero, Magali (Wiley Online Library, 2021)
Understanding the factors affecting child labor and school attendance are primordial to developing policies aimed at improving the lives of children. Policies are needed as poor households can sub-invest in human capital. Factors have individually shown to affect child labor and school attendance, but we question which factors cause the strongest effects by considering them simultaneously. We evaluate which factors have led to the decrease in child labor and the increase in school attendance of children aged 12-14 in Mexico. We consider income, the education of the head-of-household, monetary government transfers, access to public health institutions, remittances and demographic characteristics, as possible sources of the changes. We use a variant of the Oaxaca-Blinder decomposition (Fairlie, 2005), which allows the decomposition in the case the variables to be explained are dichotomous. The change in child labor and school attendance over time can then be decomposed into an explained and an unexplained portion, with each factor contributing a specific amount to the explained portion of the difference. The most important factor that led to the fall child labor and the increase in school attendance was the improvement in the human capital of parents, measured as years of education. The increase in government assistance and greater access to social health insurance also play an important role. Public policies aimed at increasing school attendance and those aimed at reducing child labor should consider the improvement of education as a major goal.